FeynMG: Automating particle physics calculations in scalar-tensor theories - Sevillano Munoz, Sergio (2023)
This thesis explores the automation of the analysis of scalar-tensor theories at subatomic scales. For this, we make use of the fact that, when appended to the Standard Model, these theories can be expressed as standard gravity plus a Beyond the Standard Model theory. Therefore, studying the modifications that scalar-tensor theories have on a matter sector in this description requires the use of quantum field theory.